PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS DAN MOTIVASI TERHADAP KINERJA PENGURUS UAM FEB UNIVERSITAS ISLAM MALANG PADA TAHUN 2017 - Danang Saputra; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThe research is to describe the style of the democratic leadership, motivation and performance of the Executive Board as well as to know the influence of democratic leadership style, motivation and performance of the Executive Board partially, This research method using the method quantitative. This research type is explanatory research. The sample of this research is the caretaker of the UAM FEB Islamic University of Malang by using sampling of saturated, i.e. as many as 70 respondents. Method of data collection using the questionnaire. Methods of analysis used in the study of multiple regression analysis SPSS 14.0 for windows. The results of this research indicate that: (1) there is a significant and positive influence of democratic leadership style against the performance of UAM FEB Islamic University of Malang. (2) there is significant motivation and a positive influence on performance UAM FEM Islamic University of Malang.Keywords: Democratic leadership Styles, motivation and performance of the Executive Board.